2003
DOI: 10.1182/blood-2002-09-2924
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of human β2-microglobulin transactivation in hematopoietic cells

Abstract: ␤ 2 -Microglobulin (␤ 2 m) is a chaperone of major histocompatibility complex (MHC) class I (-like) molecules that play a central role in antigen presentation, immunoglobulin transport, and iron metabolism. It is therefore of importance that ␤ 2 m is adequately expressed in cells that perform these functions, such as hematopoietic cells. In this study, we investigated the transcriptional regulation of ␤ 2 m in lymphoid and myeloid cell lines through a promoter containing a putative E box, Ets/interferon-stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 50 publications
6
58
0
1
Order By: Relevance
“…Third, EMSA experiments showed that it was 59 eISRE, not ISRE2, that could bind to the IFN-g-induced nuclear proteins efficiently. Similar to our present findings, the ISRE of several ISGs, such as guanylate-binding protein (GBP), IL-12, b 2 -microglobulin, and caspase-8 (34,(40)(41)(42), also has the features of an eISRE, although the contribution of the sequence adjacent to the conventional ISRE for the IFN inducibility of those ISGs has not been determined. Additionally, there also exist differences in DNA sequence between the 59 eISRE of TRIM22 and the eISRE of other ISGs.…”
Section: Discussionsupporting
confidence: 75%
“…Third, EMSA experiments showed that it was 59 eISRE, not ISRE2, that could bind to the IFN-g-induced nuclear proteins efficiently. Similar to our present findings, the ISRE of several ISGs, such as guanylate-binding protein (GBP), IL-12, b 2 -microglobulin, and caspase-8 (34,(40)(41)(42), also has the features of an eISRE, although the contribution of the sequence adjacent to the conventional ISRE for the IFN inducibility of those ISGs has not been determined. Additionally, there also exist differences in DNA sequence between the 59 eISRE of TRIM22 and the eISRE of other ISGs.…”
Section: Discussionsupporting
confidence: 75%
“…[40][41][42][43] Recently, PPARd and BCL-6 have been demonstrated to regulate MCP1 (CCL2) monocyte chemokine transcription. 44,45 IRFs, [46][47][48] …”
Section: Transcription Factorsmentioning
confidence: 99%
“…Five ODNs were synthesized, purified and tested for duplex formation [ Table 1 and supporting information (SI) Table 2]. These ODNs included: (i) ODN1 bearing human ␤2-microglobulin B box sequence (5Ј-GGAAAGTCCC-3Ј) (24), which was used primarily as a control for (ii) ODN2, which had a novel internucleoside phosphate triethylene glycol amino linker positioned after the first thymidine within 5Ј-GGAAAGTCCC-3Ј binding sequence; ODN2 was used to prepare covalent conjugates with Cy7 and 800CW dyes; (iii) complementary ODN3 that had a 3Ј-dithiopropyl linker for conjugating fluorochromes using corresponding maleimides; ODN3 was used to synthesize conjugates with Cy5.5; (iv) ODN4 having a truncated NF-B p50 binding site GGAAAG and internucleoside phosphate triethylene glycol amino linker positioned five bases downstream from the last guanine in the binding site; (v) a complementary ODN5 that was similar to ODN3 in that it also had a 3Ј-dithiopropyl linker. These ODNs were characterized by electrospray mass-spectrometry, which showed a good correlation between the calculated and observed m/z values ( Table 1).…”
Section: Resultsmentioning
confidence: 99%